Motivation For The Application Of Tqm In The Institutes Of Science And Technology Of Physical And Sports Activities - Metarfi Khemissi; Merniz Amina (sports creativity, 2025)
The aim of this study was to find out the rationale behind the application of TQM in the institutes of science and technology of physical and sports activities from the point of view of administrators at the Institute of Science and Technology of physical and sports activities at the University of M’sila. The study relied on the analytical descriptive approach as it fits the subject of the study. On a research sample consisting of 31 employees of the Institute of Science and Technology of physical and sports activities at the University of M’sila. • All the hypotheses have been achieved for the Administrative Institute of Science and Technology of physical and sports activities at the University of M’sila. .